(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In a literary work, especially in lyrics, the role of artistic devices in conveying the content of the work is paramount. Poets reflect the diverse experiences of the human spiritual world through artistic depiction. Artistic techniques ensure the beauty of the internal form and enhance the emotional impact of the work.